1 / 12

# Multiplying Polynomials - PowerPoint PPT Presentation

Multiplying Polynomials. How Do you find the area of a rectangle? . How would you find the area of this house lot?. x ² . 2x. 5x. 10. x ² + 2x + 5x + 10 = x ² + 7x + 10. Find The Area of the Lot. 3x. 5. 2x. 6x ² . 10x. 8. 24x. 40. 6x ² + 24x + 10x + 40 =

I am the owner, or an agent authorized to act on behalf of the owner, of the copyrighted work described.

## PowerPoint Slideshow about ' Multiplying Polynomials' - pete

Download Policy: Content on the Website is provided to you AS IS for your information and personal use and may not be sold / licensed / shared on other websites without getting consent from its author.While downloading, if for some reason you are not able to download a presentation, the publisher may have deleted the file from their server.

- - - - - - - - - - - - - - - - - - - - - - - - - - E N D - - - - - - - - - - - - - - - - - - - - - - - - - -
Presentation Transcript

### Multiplying Polynomials

How Do you find the area of a rectangle?

• How would you find the area of this house lot?

2x

5x

10

x² + 2x + 5x + 10 =

x² + 7x + 10

3x

5

2x

6x²

10x

8

24x

40

6x² + 24x + 10x + 40 =

6x² + 34x + 40

Example 1: Find the product of (3x + 5) (5x – 10)

3x

+5

5x

25x

15x²

-10

-30x

-50

15x² - 30x + 25x - 50 =

15x² - 5x - 50

(3x + 5) (5x – 10) Using The FoIL Method*only used when multiplying 2 binomials

F – First

O- Outer

I – Inner

L - Last

• First: first number times the first number

(3x +5) (5x–10)

3x(5x)

= 15x²

• Outer: Outer number times the outer number

(3x +5) (5x–10)

3x(–10)

= -30x

• Inner: inner number times the inner number

(3x +5) (5x–10)

5(5x)

= 25x

• Last: Last number times the last number

(3x +5) (5x–10)

5(–10)

= -50

• F: 15x²

• O: -30x

• I : 25x

• L: -50

15x²- 30x + 25x - 50 =

15x² - 5x - 50

Example 2: Find the Product of (4x – 9)(x – 11)

= 4x² -53x +99

Example 3: Find the Product of (5x – 4)(5x + 4)

= 25x² - 16

Example 4: Find the Product of (3x + 9)(3x +9)

= 9x² + 54x + 81

Example 5: Find the Product of (2x² – 2x + 12)(-5x – 1)

-5x

-1

2x²

-10x³

-2x²

10x²

2x

-2x

-60x

12

-12

= -10x³

+8x²

-58x

-12

(2x² – 2x + 12)(-5x – 1)

2x²(-5x) +

2x²(-1)

-2x(-5x)

-2x(-1)

+12(-5x)

+12(-1)

= -10x³

-2x²

+10x²

+ 2x

-60x

-12

= -10x³

+ 8x²

- 58x

- 12

Find the product of:A) (xy)²b) (x + y)²c) (x – y) ²d) (X +y) (x – y)

=x²y²

=x² + 2xy +y²

=x² - 2xy +y²

=x² - y²